Trade and poverty allevation: The case of Bangladesh apparel sector - Hoque, Anwarul; Chowdhury, Tanzir A. (BRAC University, 2010)
Least developed countries beset with poverty are liberalizing trade policies with growth objectives. Trade contributions to economic growth are established, but impacts of liberalized trade policies on poverty have not been fully assessed. The impacts can be assessed at the micro-level through identifying the linkages between trade and poverty alleviation. In this paper the export-oriented Bangladesh apparel sector, the phenomenal growth of which came about through unilateral liberalized trade policies and quota-driven market access to developed countries under multilateral Multi Fiber Arrangement, has been studied as a case to observe if it contributed to poverty alleviation. The study revealed that the apparel sector has been very effective in reducing poverty by creating income-earning employment for unskilled workers, particularly women. However, the demise of the Multi Fiber Arrangement next year will severely affect the apparel sector’s ability for poverty reduction unless protection to employment and income of the garment workers is assured through market access by the developed countries.